PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN PENERAPAN MATEMATIS SISWA KELAS VII A SMPN 2 BOJONG DALAM PTM TERBATAS - Natasya Sri Rejeki Fadilah; M. Afrilianto (IKIP Siliwangi, 2022)
The focused research aims to study the improvement of students' mathematical understanding skills through discovery learning models on fractional numbers. The implementation is applied to smpn 2 Bojong students who focus on class VII in the 2021/2022 school year as many as 25 people. The required test instrument is a mathematical comprehension ability test of 6 descriptions. The research was conducted in a series that contains two cycles with two encounters in each cycle. The final data of completion is analyzed based on the quality that goes through the phases consisting of: 1. Accumulated data, 2. Data shrinkage, 3. Data submission, and 4. Summary. The non-test assessment used is a scale of learning independence attitudes. The impact of the first cycle of research shows that students are still passive and learning is not effective because learning is solidified. In the pretest results, the average value is 39 which is still far from the KKM value of 70. After analysis, many students of class VII A still do not understand the concept of fractional number operations. At the end of the implementation of PTK, postes were carried out which had an average value of 78.4.